Tear hypoxia-inducible factor-1α expression, lactate dehydrogenase, and malate dehydrogenase activity changes in soft contact lens wear (Faculty of Medicine Universitas Indonesia, 2020)
BACKGROUND Soft contact lens (SCL) wear can lead to a corneal hypoxia. However, there is a lack of studies looking for corneal hypoxia biomarkers in tear. This study aimed to investigate corneal hypoxia among SCL wearers based on hypoxia-inducible factor-1α (HIF-1α) expression, tear lactate dehydrogenase (LDH), and malate dehydrogenase (MDH) activities. METHODS A nonrandomized clinical trial was conducted on two groups. SCLs were prescribed for 2 months to a group of new wearers. Meanwhile, SCL wear was discontinued for 1 month in a group of long-term wearers. Tear samples were then collected on days 1, 7, 14, 28, and 56 after treatment. Repeated-measures analysis of variance and Friedman’s test with post-hoc statistical analysis were used to evaluate biomolecular changes (HIF-1α concentration, LDH, and MDH activities) in both groups. RESULTS A total of 14 subjects (28 eyes) were enrolled in each group. In new wearers, there was a significant decrease in MDH level (p = 0.010) and no effect on HIF-1α level. In long-term wearers, HIF-1α and LDH levels tended to decrease (p = 0.054). A significant decrease on MDH level was noted on days 7 (p = 0.003), 14 (p = 0.026), and 28 (p<0.010). Long-term wearers had a higher LDH baseline level than new wearers (p = 0.04). CONCLUSIONS Corneal hypoxia was not proven after 2 months of SCL wear using biomarkers. However, LDH and MDH activities in tears were found to be decline after SCL discontinuation.